Safety Instrumented Systems between Reliability and Fuzzy - Rachid, Ouache; Ali, A. J. Adham (FTMS Global, 2014)

(untitled)
Quantitative risk assessment and reliability are essential issues in modern safety to make reliable decision, and it is new approach used for risk management to identify accident scenarios that may occur at their facilities which are sources of damage. Risk assessment of safety instrumented systems is approaches designed primarily to reduce the existing risk inherent in engineering system to a level considered tolerable and maintain it over time. In this study, the reliability of quantitative risk assessment using fuzzy sets based on event tree analysis and layer of protection analysis is the model proposed to deal with inaccuracy and uncertainty of data. The model proposed to determine the severity of the scenario and determine the safety integrity level SIL using Fuzzy Sets theory. The results which have got by this model is more motivate to deal with uncertainty of which considered as complementary for logical and arithmetic computation.